2016
DOI: 10.1111/jsr.12426
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in European patients with obstructive sleep apnea: the ESADA cohort study

Abstract: The cross-sectional relationship of obstructive sleep apnea with moderate to severe chronic kidney disease, defined as an estimated glomerular filtration rate <60 mL min ∙1.73 m , was investigated in a large cohort of patients with suspected obstructive sleep apnea studied by nocturnal polysomnography or cardiorespiratory polygraphy. Data were obtained from the European Sleep Apnea Database, where information from unselected adult patients with suspected obstructive sleep apnea afferent to 26 European sleep ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 36 publications
5
54
0
Order By: Relevance
“…In general, SDB produces an impaired quality of life, including an increased risk of causing motor-vehicle accidents. SDB also increases the mortality rate [9], because it contributes to the development of cardiovascular diseases [10] such as hypertension [11], type 2 diabetes [12], cancer [13], and chronic kidney disease [14]. Because it is associated with many co-morbidities [15], SDB has several distinct clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, SDB produces an impaired quality of life, including an increased risk of causing motor-vehicle accidents. SDB also increases the mortality rate [9], because it contributes to the development of cardiovascular diseases [10] such as hypertension [11], type 2 diabetes [12], cancer [13], and chronic kidney disease [14]. Because it is associated with many co-morbidities [15], SDB has several distinct clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Marrone et al demonstrated in a cohort of patients (from the European Sleep Apnea Database) that the combination of severe OSA and nocturnal hypoxemia might be an important risk factor for kidney dysfunction. 5 We have read with great interest the letter of Chung et al 6 wherein they highlighted the deleterious influence of nocturnal hypoxemia on the postoperative complication rate. Their letter confirmed to us that future studies must be specifically designed to recognize the possible influence of the nocturnal hypoxemia/severe OSA combination vs nocturnal hypoxemia alone or severe OSA alone.…”
Section: To the Editormentioning
confidence: 99%
“…One consequence was that in most subjects under investigation OSA, when present, was mild or moderate and, more than else, characterised by mild oxygen desaturations. Studies that found a relationship between hypoxemia and kidney function usually had populations where severe or protracted hypoxic levels were reached (6,7,9,10,16). Conversely, other studies reporting no effect of hypoxemia mainly included subjects with mild respiratory disorders and desaturations (8).…”
Section: Editorialmentioning
confidence: 99%
“…In clinical populations of suspected OSA patients, the link between OSA and CKD appeared stronger in female subjects (9,14). One limitation of Adams' study is that it cannot provide any information on possible gender-related differences in the general population, since it included only male subjects (26).…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation